HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERAN PERAWAT DALAM PENATALAKSANAAN LANJUTAN PASIEN STROKE ISKEMIK AKUT PASCA PEMBERIAN TERAPI rTPA DI RUANGAN ICU DAN HCU RSSN BUKITTINGGI TAHUN 2018 - Aldo Yuliano; Okta Argaen; Ida Suryati (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Acute ischemic stroke assosiated with disability has an event incidence 10 times higher than hemoragic. rTPA trombolysis therapy is the special management of acute ischemic stroke that intends to reperfusing the brain blood vessels to prevent the serious neurological damage if it do on the window time. The nurses leave mayor role in the stroke team, so the nurses that have duty in the stroke unit specially in IGD, ICU, and HCU should have knowledge and skills to care for stroke patients, especially for acute ischemic stroke patients after rTPA therapy. This study aims to determine the relation between nurse knowledge and attitude with nurse role in advanced management of acute ischemic stroke patients after rTPA therapy in ICU and HCU room RSSN Bukittinggi in 2018. This research used cross sectional descriptive correlation design. The sample of this research were 42 nurses in ICU and HCU RSSN Bukittinggi. This research used non probality sampling method of sampling. nurse knowledge obtained p value = 0,040, nurse attitude obtained p value = 0,002 with OR = 12,600. It was concluded that nurse knowledge and nurse attitudes were statistically related to the role of nurses in the continued management of acute ischemic stroke patients post-rTPA therapy. It is recommended to RSSN Bukittinggi to provide training on the management of rTPA therapy.